Strategi Transformasi Digital dan Kapabilitas Dinamis dalam Mencapai Keunggulan Bersaing Berkelanjutan pada Era Disrupsi (Studi Kasus pada Sektor Manufaktur dan Jasa di Indonesia) - Putri, Tri Anada; Safira, Muthia; Arif, Budi; Syafwandi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Amidst technological disruption and business environment uncertainty, digital transformation has become a crucial factor in building sustainable competitive advantage. This study aims to analyze the impact of digital transformation on sustainable competitive advantage, with dynamic capabilities serving as a mediating variable. An explanatory quantitative approach was employed, utilizing data obtained from a survey of 145 middle and senior-level managers in Indonesia's manufacturing and service sectors. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with a bootstrapping procedure involving 5,000 resamples. The results indicate that digital transformation has a positive and significant effect on both dynamic capabilities (β = 0.584; t = 8.412; p < 0.001) and sustainable competitive advantage (β = 0.312; t = 3.825; p < 0.001). Dynamic capabilities also exert a positive and significant influence on sustainable competitive advantage (β = 0.428; t = 5.194; p < 0.001). Furthermore, the indirect effect of digital transformation on sustainable competitive advantage through dynamic capabilities is significant (β = 0.250; t = 4.310; p < 0.001). These findings demonstrate that dynamic capabilities act as a mediator in the relationship between digital transformation and sustainable competitive advantage